Factors Affecting Millennials' Perspective on Investment Decision Behavior during the Pandemic - Singh, Amarjeet (Future Science / FSH-PH Publications, 2022)
Investor decision behavior in any pandemic, Covid-19 always goes through rationally. In reality or practically, the investment decisions made by millennials (generation Y) are not always rational. The sole purpose of the topic under study is to investigate a spectrum of millennial (generation Y) investors’ behavioral factors that affect investment decisions during a pandemic. This study adopted secondary sources for data collection. The secondary data is gathered through published research papers in peer-reviewed journals, scholarly journals, magazines, news, and books, as well as published data from the government. The major findings reveal that millennials (generation Y) financially deal with more confusion and disagreements when dealing with various patterns of informed conduct or behavior in contrast to other generations. Also, if taken a step further, the outcomes imply a much more important aspect regarding investors' behavior, financial investments, and economic growth: that they were all affected by the Covid-19 pandemic. It caused anxiety and uncertainty among players in the market. Behavioral factors and heuristics like the overconfidence and attitude effect, and herding factors are considered to have also influenced investors' decisions. Furthermore, the market behavior factors of price change, market information, past trend, customer preference, and underlying stock fundamentals have an impact on individual investor decision behavior.